Changes in serum interleukin-2, -6, and -8 levels before and during treatment with risperidone and haloperidol: relationship to outcome in schizophrenia - Zhang, Xiang Yang; Zhou, Dong Feng; Cao, Lian Yuan; Zhang, Pei Yan; Wu, Gui Ying; Shen, Yu Cun (The journal of clinical psychiatry, 2004)
Many studies have indicated that immune cytokines may be involved in the pathophysiology of schizophrenia. Recently, there have been reports that typical and atypical antipsychotic drugs may influence the levels of cytokines or cytokine receptors. The aim of this study was to compare the effect of typical and atypical antipsychotic drugs on serum interleukin-2 (IL-2), interleukin-6 (IL-6), and interleukin-8 (IL-8) and to investigate the relationship between the changes in cytokines and the therapeutic outcome in schizophrenia. From April 1996 to August 1997, seventy-eight inpatients with a diagnosis of chronic schizophrenia (DSM-III-R) were randomly assigned to 12 weeks of treatment with 6 mg/day of risperidone or 20 mg/day of haloperidol. Clinical efficacy was determined using the Positive and Negative Syndrome Scale. Serum IL-2 was assayed by radioimmunometric assay, and serum IL-6 and IL-8 concentrations were measured by quantitative enzyme-linked immunosorbent assay in patients and 30 sex- and age-matched normal subjects. Both risperidone and haloperidol reduced the elevated serum IL-2 concentrations in schizophrenia, and no significant difference was noted in the reduction of serum IL-2 concentrations between risperidone and haloperidol treatment. Neither risperidone nor haloperidol showed significant influence on the higher serum IL-6 or IL-8 concentrations in schizophrenia. Correlations between serum IL-2 or IL-8 concentrations at baseline and the therapeutic outcome were observed, demonstrating that patients presenting with low concentrations of serum IL-2 or IL-8 at baseline showed greater improvement and patients presenting with higher serum IL-2 or IL-8 concentrations at baseline showed less improvement after treatment. Both typical and atypical anti-psychotic drugs may at least partially normalize abnormal immune alterations in schizophrenia. Some immune parameters at baseline may be useful for predicting the neuroleptic response of schizophrenic patients.